Analisis Pengalaman Pengguna Terhadap Trotoar di Koridor Jalan Brigjen Katamso, Medan - Waluyo, Muhammad Denri; Moerni, Saufa Yardha (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
A corridor is a path or road that has an important role in supporting the mobility and activities of the surrounding community. The Jalan Brigjen Katamso corridor in Medan City is said to be one of the main roads that are important for the daily life of the local community. Street elements are components or features found along the road that support the comfort and safety of road users, especially pedestrians. What is meant by street elements includes vegetation (plants and trees), street furniture (street furniture such as benches, street lights, and garbage cans), as well as regular parking arrangements. This study aims to analyze the design pattern of street elements in the Jalan Brigjen Katamso corridor based on pedestrian perception. Through observation and questionnaires, this study identifies various problems and pedestrian needs related to street elements along the road corridor. The results of the research in designing the street elements in this road corridor have not been optimal, causing various problems. Lack of vegetation, inadequate street furniture, and chaotic parking arrangements cause inconvenience to pedestrians and other road users. The results of this study are expected to provide comprehensive recommendations to the government and related parties to improve the quality of the Brigadier General Katamso Road corridor. This recommendation is expected to realize a pedestrian-friendly, aesthetic, and sustainable road corridor, so that it can provide direct benefits to residents and the surrounding environment and improve the overall quality of life